Timely diagnostics and safe procedures in children with anterior mediastinal masses (AMMs): a qualitative review of the AMM protocol at BC Children's Hospital in Vancouver BC. (2nd January 2023) - Bohm, Alexandra; Campbell, Caleigh; Peters, Cheryl; Datoo, Natasha
Abstract: The presence of an anterior mediastinal mass should prompt rapid triage, workup and treatment to effectively manage and prevent emergent complications. Implementation of an AMM protocol can ensure the response is standardized and coordinated. Importantly, such a protocol can encourage prompt multi-disciplinary communication to mitigate risks associated with procedures required for timely diagnosis. The aim of this review is to evaluate the BC Children's Hospital's Pediatric New/Suspected Anterior Mediastinal Mass (AMM) Protocol. Retrospective chart review was conducted for 18 patients admitted from February 2016 to May 2020 with AMM for whom the protocol was enacted. Primary parameters assessed presence of high-risk feature at time of presentation, time from admission and/or protocol activation to specific time points, including imaging, first diagnostic procedure, and diagnosis. Data regarding perioperative management, including anesthetic considerations and peri-operative complications, was also collected. Mean time from protocol activation to first diagnostic procedure and diagnosis were 1.88 days (range 0–7) and 2.24 days (range 0–7), respectively. The majority of procedures were conducted under sedation ( n  = 77, 64%), followed by general anesthetic (GA; n  = 34, 28%) and local anesthetic ( n  = 10, 8%). Despite 15 cases having more than one high risk feature, pre-operative steroids were only administered for four of the total 158 procedures (3%) and extracorporeal life support (ECLS) and otolaryngology (ENT) were only required for immediate availability for seven procedures (4%). Furthermore, only 10 procedures (8%) had associated complications and none of these complications resulted in patient death. Our data demonstrate that implementation of a streamlined multi-disciplinary protocol can expedite time to diagnosis without impacting patient safety.